2006
DOI: 10.1523/jneurosci.1251-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Intracellular Trafficking of Huntingtin-Associated Protein-1 Is Critical for TrkA Protein Levels and Neurite Outgrowth

Abstract: Mutant huntingtin can affect vesicular and receptor trafficking via its abnormal protein interactions, suggesting that impairment of intracellular trafficking may contribute to Huntington's disease. There is growing evidence that huntingtin-associated protein-1 (HAP1) also interacts with microtubule-dependent transporters and is involved in intracellular trafficking. However, it remains unclear how the trafficking of HAP1 is regulated and contributes to neuronal function. Here we report that phosphorylation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
108
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(113 citation statements)
references
References 46 publications
5
108
0
Order By: Relevance
“…Thus, we concluded that Hap1 not only sequesters but also stabilizes Dcaf7 in the cytoplasm by inhibiting its degradation by the UPS. Because Hap1 can protect internalized receptors from lysosomal degradation (11,(29)(30)(31), Hap1 may stabilize its binding partners from subsequent degradation through either the lysosome or UPS.…”
Section: Hap1 Stabilizes the Protein Level Of Dcaf7 By Inhibiting Itsmentioning
confidence: 99%
“…Thus, we concluded that Hap1 not only sequesters but also stabilizes Dcaf7 in the cytoplasm by inhibiting its degradation by the UPS. Because Hap1 can protect internalized receptors from lysosomal degradation (11,(29)(30)(31), Hap1 may stabilize its binding partners from subsequent degradation through either the lysosome or UPS.…”
Section: Hap1 Stabilizes the Protein Level Of Dcaf7 By Inhibiting Itsmentioning
confidence: 99%
“…Another possible role for spartin in neurons may be in the internalization, sorting, and/or degradation of specific receptors for neurotrophic factors such as BDNF or NGF, which are important for cell survival and neurite outgrowth. Interestingly, a number of proteins mutated in neurological disorders, including alsin, huntingtin, and parkin, have roles in endocytosis (Devon et al, 2006;Fallon et al, 2006;Rong et al, 2006). It remains to be determined whether lack of spartin affects endocytosis of growth factor receptors, which might lead to deficiency in survival signals and impaired neurite outgrowth.…”
mentioning
confidence: 99%
“…HTT protein is a scaffolding protein that regulates multiple aspects of trafficking of transmembrane receptors, including endocytosis (82), endosomal sorting (83), anterograde transport (71,84), degradation (71,83,84), and recycling (85,86). It has been shown that mtHTT can inhibit the surface expression of receptors via its interactions with trafficking proteins such as Rab11 (87) and HAP1 (71,83,84), proteins that prevent lysosomal degradation and promote recycling of their cargo receptors back to the cell surface (88). For example, mtHTT can bind to and interfere with the nucleotide exchange activity of Rab11, a small GTPase that functions at recycling endosomes, and impede the membrane recycling of its cargo such as transferrin receptor (89), solute carrier EAAC1 (87), and glucose transporter 3 (90).…”
Section: Discussionmentioning
confidence: 99%
“…For example, mtHTT can bind to and interfere with the nucleotide exchange activity of Rab11, a small GTPase that functions at recycling endosomes, and impede the membrane recycling of its cargo such as transferrin receptor (89), solute carrier EAAC1 (87), and glucose transporter 3 (90). mtHTT also binds more tightly to HAP1 compared with wtHTT, thereby disrupting the synaptic targeting of GABA A receptor (83) and the anterograde trafficking of TrkA receptor (84).…”
Section: Discussionmentioning
confidence: 99%